Preparation method of polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function
Through polymer/Ti3C2-CeO2 composite scaffold combined with nanoenzyme catalysis and photothermal therapy, the problems of tumor cell residues and bone defects in osteosarcoma treatment were solved, the anti-tumor efficiency and bone repair effect were improved, and the bone tumor resection was achieved after bone tumor resection Effective prevention and repair.
Patent Information
- Application Number
- CN202411420787.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
In the treatment of osteosarcoma, surgery is difficult to completely remove tumor cells, chemotherapy has poor targeting, drug resistance and side effects, and the existing bone stent lacks anti-tumor function, resulting in high recurrence and metastasis, and photodynamic therapy is limited by hypoxia and Glutathione overexpression.
Using polymer/Ti3C2-CeO2 composite scaffolds, nanoenzyme catalysis, photothermal and photodynamic therapy can be used to improve anti-tumor efficiency, use CeO2 to catalyze oxygen and consume excessive glutathione, and combine with the photothermal effect of Ti3C2 to enhance enzyme activity, and prepare Bone defect repair material with anti-tumor function is produced.
It improves the specificity and controllability of photodynamic therapy, enhances anti-tumor efficiency, promotes bone tissue repair, reduces treatment side effects, and realizes bone defect repair and tumor prevention after bone tumor resection.
Smart Images

Figure CN119280472A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and more specifically, relates to a method for preparing a polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function. Background Art
[0002] Osteosarcoma refers to a malignant tumor in which tumor cells can directly form tumorous osteoid tissue or bone tissue. It accounts for about 20% to 34% of all primary malignant bone tumors and is the most common malignant primary bone tumor. Osteosarcoma can occur at all ages, but is most common in people aged 11 to 20 years old, followed by those aged 21 to 30 years old. The recurrence rate, metastasis rate, mortality rate and disability rate of osteosarcoma are all high.
[0003] At present, the treatment of osteosarcoma is mainly surgery and bone implantation combined with systemic chemotherapy. However, it is difficult to completely eliminate tumor cells through surgery, which leads to tumor recurrence and metastasis. Chemotherapy drugs need to be administered systemically, and have disadvantages such as poor targeting, drug resistance, rapid drug clearance, unstable blood drug concentration, and may also bring side effects such as bone marrow suppression. These limitations lead to the final treatment effect of osteosarcoma is not ideal, and the patient's 5-year survival rate has not improved much in decades. Therefore, there is an urgent need for effective and low-side effect treatment strategies to treat osteosarcoma. In recent years, bone scaffolds with osteogenic ability have been continuously developed, but there is an urgent need for scaffolds that have both osteogenesis and excellent anti-tumor functions to achieve the purpose of repairing bone defects and killing residual tumor cells after bone tumor resection.
[0004] In recent decades, treatments based on reactive oxygen species (ROS), such as photodynamic therapy (PDT), sonodynamic therapy (SDT), and chemodynamic therapy (CDT), have become emerging therapeutic strategies for malignant tumors. High concentrations of reactive oxygen species can disrupt cellular redox homeostasis, induce oxidative stress, lead to DNA damage, lipid peroxidation, and protein oxidation, and thus cause cell death or apoptosis. Photodynamic therapy is a clinically approved cancer therapy. Under laser irradiation of a specific wavelength, photosensitizers are activated, and the excited photosensitizers transfer energy to the surrounding oxygen to generate highly reactive singlet oxygen, which in turn causes damage to tumor cells or even death. Singlet oxygen is highly reactive, with a lifetime of approximately 40 ns and a maximum action radius of approximately 20 nm. This short action radius (smaller than the diameter of most organelles) and local photosensitizer activation by irradiating only the target tissue theoretically make photodynamic therapy highly specific and controllable. However, the tumor microenvironment, characterized by hypoxia and glutathione overexpression, severely limits the effectiveness of photodynamic therapy. Therefore, exploring strategies to improve hypoxia and promote glutathione depletion is of great significance for improving the efficacy of photodynamic therapy.
[0005] Nanozymes are defined as nanomaterials that can catalyze chemical reactions involving enzyme substrates under physiological conditions by following enzyme kinetics, and have both the unique properties of nanomaterials and the catalytic activity of enzymes. Compared with natural enzymes, nanozymes have the advantages of adjustable activity, high stability, low cost, easy preparation and storage. In biomedical applications, common enzyme mimic activities are mostly redox-type, and can be divided into peroxidase-like, oxidase-like, catalase-like and superoxide dismutase-like according to their catalytic mechanism. Nanozymes can respond to specific tumor microenvironments such as weakly acidic pH, H2O2, enzymes, hypoxia and high concentrations of glutathione, and thus show great potential in regulating the tumor microenvironment and have relatively high specificity and low toxic side effects in tumor treatment. For example, nanozymes with catalase-like activity can catalyze endogenous substances in tumor tissues to produce oxygen to improve hypoxia. Nanozymes can also consume overexpressed glutathione through inherent redox reactions. Therefore, nanozyme catalytic therapy is expected to be used to solve the problem of hypoxia and overexpression of glutathione in the tumor microenvironment. Summary of the invention
[0006] The present invention aims to solve the problem of bone defects in the surgical area and residual tumor cells in the original lesion after bone tumor resection, and provides a method for preparing a polymer / Ti3C2-CeO2 composite scaffold material with anti-tumor function. The purpose is to provide a bone defect repair material that can prevent the recurrence and metastasis of bone tumors in patients and improve the prognosis of patients. Specifically, nanozymes are used to remove the limitations of hypoxia and glutathione overexpression in the tumor microenvironment on the efficacy of photodynamic therapy, and nanozyme catalysis, photothermal and photodynamic therapy are combined to synergistically improve the anti-tumor efficiency.
[0007] In order to achieve these purposes according to the present invention, a method for preparing a polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function is provided. First, CeO2 is grown in situ on the surface of Ti3C2 to prepare Ti3C2-CeO2 powder, and then the high molecular polymer powder and Ti3C2-CeO2 powder are evenly mixed by grinding according to a proportion, and then the polymer / Ti3C2-CeO2 scaffold is prepared by selective laser sintering technology.
[0008] Preferably, the high molecular polymer powder is at least one of left-handed polylactic acid (PLLA) powder, right-handed polylactic acid (PDLA) powder, optically inactive polylactic acid (Meso-PLA) powder, racemic polylactic acid (PDLLA) powder, polycaprolactone (PCL) powder, polyglycolide (PGA) powder, polylactide (PLA) powder, poly(lactide-glycolide) (PLGA) powder and poly(p-dioxanone) (PPDO) powder.
[0009] Preferably, in the polymer / Ti3C2-CeO2 scaffold, the mass fraction of the high molecular polymer powder is 90-98wt%, the mass fraction of the Ti3C2-CeO2 powder is 2-10wt%, the particle size of the Ti3C2-CeO2 powder is 0.2-1μm, and the particle size of the high molecular polymer powder is 0.1-100μm.
[0010] Preferably, the method comprises the following steps:
[0011] Step 1: Based on the hydrothermal synthesis method, cerium nitrate is used as a precursor, polyvinyl pyrrolidone is used as a dispersant, and sodium hydroxide is used as a pH regulator to synthesize Ti3C2-CeO2 composite materials. The specific method includes: weighing Ti3C2, cerium nitrate, polyvinyl pyrrolidone and sodium hydroxide respectively, dissolving them in deionized water, and ultrasonically treating them for 5 to 15 minutes to ensure dissolution. The above solutions are mixed, deionized water is added to the volume, and ultrasonically treated for 10 to 40 minutes at room temperature. Subsequently, the resulting solution is transferred to a polytetrafluoroethylene-lined autoclave, and the reactor is placed at 150°C to 210°C (oven). After 4 to 8 hours, the reaction solution is taken out from the autoclave and centrifuged and washed three times with anhydrous ethanol. The centrifuged precipitate is vacuum dried and ground to obtain Ti3C2-CeO2 nanoparticles.
[0012] Step 2: Weigh polymer powder and Ti3C2-CeO2 powder in a specific mass ratio as required, place them in a container filled with anhydrous ethanol to prepare a suspension, stir, filter, dry and grind to obtain the scaffold composite material powder. Build a three-dimensional model and import it into the printer for layering, and preheat the powder. Then spread the powder evenly on the substrate of the selective laser sintering system, and the laser prints the contour according to the layering data. After one layer is sintered, spread the powder, sinter, and form the next layer of powder, and repeat this cycle, layer by layer, to finally obtain a polymer / Ti3C2-CeO2 scaffold.
[0013] Preferably, in the step 1, the mass ratio of Ti3C2, cerium nitrate, polyvinyl pyrrolidone and sodium hydroxide is 0.0596g:0.289g:0.083g:3.2g.
[0014] Preferably, in the step 2, during the selective laser sintering process, the process parameters of the selective laser sintering are: laser power of 12W to 15W, scanning speed of 100 to 300 mm / min, and scanning spacing of 0.25 to 1.0 mm.
[0015] An application of a polymer / Ti3C2-CeO2 scaffold with anti-tumor function, characterized in that the prepared polymer / Ti3C2-CeO2 scaffold is applied in the field of biomedical materials.
[0016] The present invention has the following advantages:
[0017] Compared with traditional bone tumor treatment methods, photodynamic therapy converts endogenous hydrogen peroxide in tumors into singlet oxygen to kill tumor cells under laser irradiation of a specific wavelength, so it has the advantages of non-invasiveness, strong controllability, and few side effects. Importantly, the present invention uses nanozymes to remove the limitations of hypoxia and glutathione overexpression in the tumor microenvironment on the efficacy of photodynamic therapy, and combines nanozyme catalysis, photothermal and photodynamic therapy to synergistically improve the anti-tumor efficiency. In addition, the selected Ti3C2 material has good biocompatibility, biodegradability, excellent hydrophilicity, surface functionalization and Ca2+ binding sites, especially under the interaction of water and oxygen, Ti3C2 degrades and releases titanium-based substances to promote the growth of bone tissue. The selected nano CeO2 can increase cell adhesion, promote the proliferation, differentiation and mineralization of osteoblasts, and is of great significance in the application of biomedicine. The selected high molecular polymer PLLA has the advantages of non-toxicity, non-irritation, biodegradable absorption, high strength, good plasticity, and easy processing and molding. In addition, the selective laser sintering technology of the preparation method of the artificial bone scaffold material provided by the present invention can realize personalized customization needs according to the bone defect conditions of clinical patients, and accurately match the shape of the patient's bone defect area. Moreover, it can print out a scaffold with appropriate porosity and pore size, which is conducive to cell adhesion and the exchange of nutrients and metabolites after the artificial bone scaffold is implanted, thereby improving the efficiency of bone tissue repair.
[0018] One purpose of the present invention is to kill tumor cells and cure bone tumors, and to improve the anti-tumor effect of photodynamic therapy through self-oxygen supply and glutathione depletion strategies. Ti3C2 has a large specific surface area, and Ti3C2 is selected as a carrier of CeO2 to load and disperse CeO2 to prevent CeO2 from agglomerating and reduce active sites. Based on the tumor microenvironment with high concentration of hydrogen peroxide, CeO2 exerts catalase enzyme activity, catalyzes hydrogen peroxide to produce oxygen, and provides an oxygen source for the photodynamic process of Ti3C2, which is of great significance for the generation of singlet oxygen. Moreover, this process is accompanied by the generation of Ce4+, which consumes glutathione, an antioxidant over-expressed in the tumor microenvironment through redox reactions, and promotes oxidative stress in tumor cells. Importantly, the photothermal effect of Ti3C2 in turn enhances the enzyme activity of CeO2, and Ti3C2 and CeO2 promote each other. Nanozyme catalysis and photothermal therapy and photodynamic therapy synergistically improve the anti-tumor efficiency.
[0019] Another purpose of the present invention is to promote the repair of bone defects after surgical resection of bone tumor lesions. Ti3C2 and CeO2 both have good biocompatibility and osteogenic function, and the porosity and pore size of the prepared scaffold are conducive to the adhesion and proliferation of osteoblasts.
[0020] Other advantages, objectives and features of the present invention will be partially reflected in the following description, and partly will be understood by those skilled in the art through research and practice of the present invention. The above description is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above implementation. Any equivalent modification, equivalent replacement, improvement, etc. made by those skilled in the art based on the content disclosed in the present invention should be included in the protection scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the Ti3C2-CeO2 powder prepared in Example 1 of the present invention;
[0022] Figure 2 The cell counting (CCK-8) results of co-culturing the polymer / Ti3C2-CeO2 scaffold (PLLA / Ti3C2-CeO2) and PLLA scaffold, PLLA / Ti3C2 scaffold prepared in Example 1 of the present invention with human osteosarcoma MG-63 cells for 1 day, 2 days and 3 days; DETAILED DESCRIPTION
[0023] The present invention will be further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement it with reference to the description. It should be understood that terms such as "having", "including" and "comprising" used herein do not exclude the existence or addition of one or more other elements or their combinations.
[0024] Example 1: This example provides a method for preparing a polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function, comprising the following steps:
[0025] Step 1: Based on the hydrothermal synthesis method, cerium nitrate is used as a precursor, polyvinyl pyrrolidone is used as a dispersant, and sodium hydroxide is used as a pH regulator to synthesize Ti3C2-CeO2 composite materials. The specific method includes: weighing 0.0596g Ti3C2Mxene, 0.289g cerium nitrate, 0.083g polyvinyl pyrrolidone and 3.2g sodium hydroxide, respectively, and dissolving them in 10mL deionized water, and ultrasonically treating for 10 minutes to ensure dissolution. The above solutions are mixed, deionized water is added to the total volume of the mixed solution to 80ml, and ultrasonically treated at room temperature for 30 minutes. Subsequently, the resulting solution is transferred to a polytetrafluoroethylene-lined autoclave and hydrothermally treated at 180°C (oven) for 6 hours. The reacted solution is washed with anhydrous ethanol and centrifuged three times at a speed of 6500r / min for 4 minutes; the centrifuged precipitate is placed in a vacuum environment and dried, the temperature is set to 60°C, the drying time is 12 hours, and the Ti3C2-CeO2 nanoparticles are obtained by grinding.
[0026] Step 2, prepare composite powder: PLLA and Ti3C2-CeO2 powder are fully mixed in a mass ratio of 19:1 (the mass fraction of Ti3C2-CeO2 is 5%), placed in a container filled with anhydrous ethanol to obtain a suspension, stirred, filtered, dried and ground to obtain PLLA / Ti3C2-CeO2 scaffold composite material powder.
[0027] Step 3, 3D printing bracket: Design the bracket model with 3D modeling software, save it in .stl format, import it into the 3DPrinter software, set the printing parameters: laser power 12W~15W, scanning speed 200mm / s, scanning spacing 0.5mm. Spread the evenly mixed composite powder evenly on the substrate, and obtain the PLLA / Ti3C2-CeO2 bracket after layer-by-layer sintering.
[0028] Comparative Example 1: This comparative example provides a method for preparing a PLLA scaffold. In this comparative example, 100 wt% PLLA is used as a raw material to prepare a PLLA scaffold. First, PLLA powder is placed in a grinding mortar and ground for 15 minutes to fully mix the powders to obtain a uniformly mixed PLLA powder;
[0029] 3D printing steps: Design the bracket model using 3D modeling software, save it in .stl format, import it into the 3D Printer software, and set the printing parameters: laser power 5W, scanning speed 200mm / s. Spread the evenly mixed PLLA powder evenly on the substrate, and sinter it layer by layer to obtain the PLLA bracket.
[0030] Comparative Example 2: This comparative example provides a method for preparing a PLLA / Ti3C2 scaffold. First, PLLA and Ti3C2 powders are fully mixed in a mass ratio of 19:1 (Ti3C2 mass fraction is 5%), placed in a container filled with anhydrous ethanol to prepare a suspension, and stirred, filtered, dried, and ground to obtain uniformly mixed PLLA / Ti3C2 powder.
[0031] 3D printing bracket: The bracket model was designed by 3D modeling software, saved in .stl format, imported into the software 3D Printer, and the printing parameters were set: laser power 18W, scanning speed 200mm / s. The evenly mixed PLLA / Ti3C2 powder was evenly spread on the substrate, and the PLLA / Ti3C2 bracket was obtained after layer-by-layer sintering.
[0032] The PLLA / Ti3C2-CeO2 scaffolds, PLLA scaffolds, and PLLA / Ti3C2 scaffolds prepared in this embodiment were co-cultured with human osteosarcoma cells MG-63 for 1 day, 2 days, and 3 days, respectively. Human osteosarcoma cells MG-63 were selected for the anti-tumor experiment. All scaffolds were sterilized by ultraviolet irradiation overnight before the experiment. Tumor cells were seeded in a 48-well plate at a density of 5000 per well, cultured for 12 hours until the cells adhered to the wall, and then the scaffolds were added to co-culture with them. For the near-infrared group, 808nm, 1.0W / cm -2 The cells were irradiated with laser for 10 minutes. Cell counting reagent (CCK-8) was added on the 1st, 2nd and 3rd day respectively, and the absorbance of each group at 450nm was measured after incubation in a 37°C constant temperature incubator for 6 hours.
[0033] The results of CCK8 experiments are as follows Figure 2 As shown, it can be seen that the PLLA / Ti3C2-CeO2 scaffold combined with near-infrared laser shows obvious anti-tumor effect, because CeO2 catalyzes hydrogen peroxide to produce oxygen, providing reactants for the photodynamic process of Ti3C2 under NIR, and promoting the production of singlet oxygen. Moreover, CeO2 consumes glutathione through redox reactions and promotes oxidative stress. In addition, the photothermal effect of Ti3C2 increases the enzyme activity of CeO2. Nanozyme catalysis, photothermal therapy, and photodynamic therapy synergistically improve the anti-tumor efficacy.
[0034] The number of devices and processing scales described here are used to simplify the description of the present invention. Applications, modifications and variations of the present invention will be obvious to those skilled in the art.
[0035] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function, characterized in that: First, CeO2 is in situ grown on the surface of Ti3C2 to prepare Ti3C2-CeO2 powder, then the polymer powder and Ti3C2-CeO2 powder are ground and evenly mixed according to the proportion, and then the polymer / Ti3C2-CeO2 scaffold is prepared by selective laser sintering technology.
2. The method for preparing the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function according to claim 1, characterized in that: The high molecular polymer powder is at least one of left-handed polylactic acid PLLA powder, right-handed polylactic acid PDLA powder, racemic polylactic acid PDLLA powder, optically inactive polylactic acid Meso-PLA powder, polycaprolactone PCL powder, polyglycolic acid PGA powder, polylactic acid-glycolic acid copolymer PLGA powder and polydioxanone PPDO powder.
3. The method for preparing the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function according to claim 1, characterized in that: In the polymer / Ti3C2-CeO2 bracket, the mass fraction of the high molecular polymer powder is 90-98wt%, the mass fraction of the Ti3C2-CeO2 powder is 2-10wt%, the particle size of the Ti3C2-CeO2 powder is 0.2-1μm, and the particle size of the high molecular polymer powder is 0.1-100μm.
4. The method for preparing the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1: Based on the hydrothermal synthesis method, cerium nitrate is used as a precursor, polyvinyl pyrrolidone is used as a dispersant, and sodium hydroxide is used as a pH regulator to synthesize the Ti3C2-CeO2 composite material. The specific method includes: weighing Ti3C 2、 Cerium nitrate, polyvinyl pyrrolidone and sodium hydroxide are dissolved in deionized water respectively, and ultrasonic treatment is performed to ensure dissolution. The above solutions are mixed, deionized water is added to the volume, and ultrasonic treatment is performed at room temperature to be fully mixed. The resulting solution is then transferred to a polytetrafluoroethylene-lined autoclave and subjected to hydrothermal treatment at 150° C.-210° C. for 4-8 hours. The reacted solution is washed with anhydrous ethanol and centrifuged three times. The centrifuged precipitate is dried and ground to obtain Ti3C2-CeO2 nanoparticles. Step 2: Weigh polymer powder and Ti3C2-CeO2 powder in a specific mass ratio as required, place them in a container filled with anhydrous ethanol to prepare a suspension, stir, filter, dry, and grind to obtain a scaffold composite material powder, then place the powder in a selective laser sintering system and evenly spread it on a substrate, and preheat the powder. Select the required three-dimensional model, scan the mixed powder in layers to solidify the powder material, and after one layer is sintered, spread, sinter, and form the next layer of powder. The next layer and the previous layer are sintered together, and sintered layer by layer to finally obtain a polymer / Ti3C2-CeO2 scaffold.
5. The method for preparing the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function according to claim 4, characterized in that: In the step 1, Ti3C 2、 The mass ratio of cerium nitrate is about 1:
5.
6. The method for preparing the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function according to claim 4, characterized in that: In the step 2, during the selective laser sintering process, the process parameters are: laser power is 12W to 15W, scanning speed is 100 to 300 mm / min, and scanning spacing is 0.25 to 1.0 mm.
7. The method for preparing the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function according to claim 1, characterized in that: The prepared polymer / Ti3C2-CeO2 support has a porosity of 30-80% and a pore size of 100-800 μm or more.
8. An application of a polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function, wherein the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function is prepared by the preparation method of the polymer / Ti3C2-CeO2 composite scaffold with anti-tumor function according to any one of claims 1 to 9, characterized in that: The prepared polymer / Ti3C2-CeO2 scaffold is applied in the fields related to biomedical materials.